Study on preparation technology of low-phenylalanine perilla peptide - ZHANG Tianwei; ZHANG Zhijun; ZHANG Zhiyu; ZHANG Hongyu; LI Huizhen (浙江大学学报. 农业与生命科学版, 2023)
To enrich low-phenylalanine formula food for special medical purposes, this study used perilla defatted seed meal as the raw material to optimize the double enzymatic hydrolysis process through single factor and response surface analysis, while exploring the conditions for the adsorption of free phenylalanine by activated carbon. The results showed that the optimum conditions for the preparation of low-phenylalanine peptide by double enzymatic hydrolysis of perilla protein were as follows: the neutral complex protease (pH 7.0) and aminopeptidase (pH 8.0) were used to hydrolyze perilla seed meal at 55 ℃ for 5.0 h and 5.5 h, respectively. Then, the free phenylalanine was adsorbed by 200 mesh activated carbon. Finally, the product was detected by high performance liquid chromatography, and the phenylalanine release rate in perilla protein was 96.54%, and the phenylalanine removal rate was 97.64%, and the phenylalanine content in the product was 1.10 mg/g, which could meet the national standard of National Standard for Food Safety-General Rules for Formula Food for Special Medical Purposes (GB 29922—2013). Therefore, this study provides an effective method for the preparation of low-phenylalanine formula food for special medical purposes, which is of great practical significance to promote it.